Characterization of polymer-based piezoelectric micromachined ultrasound transducers for short-range gesture recognition applications. (29th May 2019) - Gijsenbergh, Pieter; Halbach, Alexandre; Jeong, Yongbin; Torri, Guilherme Brondani; Billen, Margo; Demi, Libertario; Huang, Chih-Hsien; Cheyns, David; Rottenberg, Xavier; Rochus, Veronique
Abstract: This paper deals with the design, simulation and characterization of polymer-based piezoelectric micromachined ultrasound transducers (PMUT) (arrays) intended for short-range gesture recognition applications. The presented process flow is fully compatible with existing flat-panel display fabrication. Finite element models were developed for the evaluation of the frequency response, deflection and acoustic pressure output of single PMUT as a function of the membrane diameter. A laser Doppler vibrometer was used to measure the frequency response, membrane velocity and displacement, as well as mode shapes of the microfabricated PMUT in air. An optical microphone was used to measure the pressure emitted by a single PMUT at various distances along the normal axis of the oscillating membrane. A strong correlation between simulations and measurement results is shown. The device geometries most suitable for short-range gesture recognition purposes are selected and the radiation pattern of square arrays is analyzed using simulations. The resonance properties of single PMUT in an array are determined using measurements. An optimized array is used to demonstrate pulse-echo measurements, and the requirements for a simple gesture recognition platform are elucidated.